1982
DOI: 10.1037/0021-9010.67.4.500
|View full text |Cite
|
Sign up to set email alerts
|

Response format of the Job Descriptive Index: Assessment of reliability and validity by the multitrait–multimethod matrix.

Abstract: Good to high short-term (3-week) stability and convergent and discriminant validity of the Job Descriptive Index (JDI) were established using multitraitmultimethod matrices. Two groups (n = 50 each) responded twice to the same JDI, one with the yes/?/no format and one with a 5-point Likert-type format. Test-retest coefficients ranged from .68 to .88 and from .70 to .78, respectively. Corresponding coefficients alpha ranged from .75 to ,91 and from .80 to .93. Times 1 and 2 were treated as methods, and subscale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0
2

Year Published

1986
1986
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(71 citation statements)
references
References 17 publications
3
66
0
2
Order By: Relevance
“…Evidence of the scales' reliability and convergent and discriminant validity can be found in Johnson, Smith, and Tucker (1982). Five items were added to this scale to measure satisfaction with job security.…”
Section: Job Satisfactionmentioning
confidence: 99%
“…Evidence of the scales' reliability and convergent and discriminant validity can be found in Johnson, Smith, and Tucker (1982). Five items were added to this scale to measure satisfaction with job security.…”
Section: Job Satisfactionmentioning
confidence: 99%
“…The internal consistency coefficients were high for the Likert format with an alpha level of .87 [15] . The alternative scoring scheme, indicates little difference in providing an overall estimate of convergent validity.…”
Section: The Job Descriptive Index (Jdi)mentioning
confidence: 95%
“…The validity of the JOI was assessed through four studies in different work settings involving approximately 400 participants. Factor analyses of these studies have demonstrated substantial support for the convergent and discriminant validity of the JOI (Johnson, Smith, & Tucker, 1982;Smith, Kendall, & Hulin, 1975).…”
Section: Instrumentsmentioning
confidence: 94%